Elite swimming athlete`s career development: the perspective of the coach-athlete working alliance - Teng, P. C.; Chen, F. C.; Teng, P. Y.; Chen, M. Y.; Chang, C. C. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: With the development of sport performance, the quality of the relationship between coach and athlete is becoming more and more important. Coaches and athletes must set on goals, agreement the tasks, and accomplished the tasks to achieve the goals. This study is based on coach-athlete working alliance, discuss the interaction between coaches and athletes how to influence athletes career adaptation and career transition. METHODS: From the perspective qualitative research, this study applied in-depth interview with domestic excellent swimming coaches and the athletes they have coached. By understanding the relationship between coaches and athletes, as well as planning of athletes career adaptation and career transition, and analyzing the content of the interviews, explores the influence of the coach-athlete working alliance on career adaptation and career transition. RESULTS: The results of the study are as follows*(1) The coach will divide the goals into competitive goal and goal college entrance goal, and assign tasks to different athletes according to their abilities, coach and the athletes can feel a sense of achievement in pursuing the common goal. (2) The coach will pay attention with the athletes to focus on the career they want to work in in the future at first, and let the athletes make their decision for college, If athletes want to engage in non-sports field, they will fully show their curiosity about the careers they interested and vice versa; Compared with coaches who believe in athletes, athletes lack confidence in their careers. (3) In athletic level, the coach will enrich himself, cooperate with talents in various fields, and provide the athletes with a high-quality training environment; In psychological level, coaches not only care about active athletes, but also contact graduates through in communication software; In psychosocial level, the relationship between the athletes and the coach like a teacher as well as a friend, the athletes can maintain a good interaction even they are graduate; In academic vocational level, It is not only the coach who can help, but the graduates can also provide a lot of assistance to solve the doubts of their junior brother. DISCUSSION: Based on the conclusions of this study practical suggestions, Coaches can take the initiative to care about the athletes situation, build self-confidence, and cooperate with graduates to assist the career development of student athletes; The suggestion for Future Research can compare with different theoretical models, and expand research sample to make future research more completely.